Association of genetic variants in ULK4 with the age of first onset of type B aortic dissection - Huang, Lihong; Tang, Jiaqi; Lin, Lijuan; Wang, Ruihan; Chen, Feng; Wei, Yongyue; Si, Yi; Fu, Weiguo (Frontiers in Genetics, 2022)
Background The association between autophagy, structural alterations of the aortic wall and endothelial dysfunction in humans have yet to be fully elucidated. The family of ULK (UNC51-like) enzymes play critical roles in autophagy and development. This study aimed to evaluate the association between ULK gene family members and patient age of first type B aortic dissection (TBAD) onset. Methods The genotype data in a TBAD cohort from China and the related summary-level datasets were analyzed. We applied the sequence kernel association test (SKAT) to test the association between single-nucleotide polymorphisms (SNPs) and age of first onset of TBAD controlling for gender, hypertension and renal function. Next, we performed a 2-sample Mendelian randomization (MR) to explore the potential causal relationship between ULK4 and early onset of TBAD at the level of gene expression coupled with DNA methylation with genetic variants as instrumental variables. Results 159 TBAD patients with 1,180,097 SNPs were included. Concerning the association between the ULK gene family and the age of first onset of the TBAD, only ULK4 was found to be significant according to SKAT analysis (FDR-q=0.0140). From 2-sample MR, the high level of ULK4 gene expression was related to a later age of first onset of TBAD (β= 4.57, P = 0.0196). Conclusions: This is the first study of the ULK gene family in TBAD regarding the association with the first onset age. We demonstrated that the ULK4 gene is associated with the time of onset of TBAD based on both the SKAT and 2-sample MR analyses.